PENGEMBANGAN BAHAN AJAR SEJARAH (MODUL) BERBASIS DIORAMA MUSEUM BENTENG VREDEBURG UNTUKMENINGKATKAN KESADARAN SEJARAH SISWA KELAS XI IPS SMA NEGERI 1 KALASAN SLEMAN YOGYAKARTA - Lazmihfa, L.; Waluyo, Herman J.; Haryanto, Samsi (HISTORIKA, 2014)
This research aims to 1) The analyze and describe the condition of land in high school history teaching materials 1 kalasansleman Yogyakarta, 2) The analyse the needs of the teaching material in high school N 1 kalasansleman Yogyakarta, 3) The described the development of teaching materials vredeburg fortress based history museum to increase awareness of the history of high school students class XI IPSN 1 kalasansleman Yogyakarta, 4)Described the effectiveness of teaching materials based history museum in fort vredeburg increase awareness of the history of high school students class XI social class high school 1 kalasansleman Yogyakarta. This research method using research methods Research and Development (R&D), adapted and modified Borg & Gall. Work steps in the study include: (1) Preliminary studies, 2) Media development, (3) Implementation of media use, 4) Test the effectiveness of the product. This research was conducted at secondary school (High School) Kalasan, SlemanYogyakartan. The subject of this research is the grade XI IPS 1 as experimental class and Class XI IPS 3 as a class controls. The instruments used in this research is the now the consciousness of history and achievement test results of the study. The next test is used to  t test to tested the hypothesis.From the results t test for achievements of students obtained  thit = 3.246 than at t tab 2,015 ( significance level of 5 % ), so that can be said that t hit> t tab or 3,246 > 2,015.Through these results then can be concluded that the use of the media with learning to teaching materials ( module ) can give impact on the value of students. AchievementThe results of the test and t to consciousness history students obtained is thit = 2,353 compared on ttab 2,015 ( significance level of 5 % ), so that can be said that t hit> t tabel  or 2,353 > 2,015. Through these results then can conclude that with the use of the media in the form of modules learning can provide influence against historical awareness students.